Is employment globalizing? - Liming Chen; Jesus Felipe; Andrew J.Y. Kam; Aashish Mehta (Asian Development Bank (ADB), 2018)
We investigate the claim that national labor markets have become more globally interconnected in recent decades. We do so by deriving estimates over time of three different notions of interconnection: (i) the share of labor demand that is export induced (i.e., all labor demand created by foreign entities buying products exported by the home country) - we provide estimates for 40 countries; (ii) the share of workers employed in sectors producing tradable goods or services - 68 countries; and (iii) the ratio of the number of jobs that are either located in a tradable sector, or that are involved in producing services that are required by these tradable sectors, to all jobs in the economy, which we call the trade-linked employment share - 40 countries. Our estimates lead to the conclusion that the evidence of a large increase in the interconnections between national labor markets is far weaker than commonly asserted: levels of interconnectivity, and the direction of changes over time, vary across notions of interconnection and countries. The main reasons for this are labordisplacing productivity growth in tradable sectors of each economy and the diminishing fraction of national labor forces hired into manufacturing jobs worldwide. We also discuss the implications of our results for different policy debates that each of the three measures is associated with: international coordination of macroeconomic policies (export-induced labor demand), currency devaluations (share of workers producing tradables), and education and labor protection (trade-linked share).
Keywords: F60; F63; F66; F68; 330; employment; export induced; globalization; tradable goods; trade-linked employment